Educação e laicidade: pressupostos modernos - Sena Neto, José da Penha (2023)
This research seeks to understand the process that established the important and decisive nexus between secularity and education, as discussed by Modernity. This relationship not only shaped a new pedagogical model but also became central to the understanding of Modernity itself. It is important to clarify that the interpretation of the link between secularity and education will be guided by the understanding of the conflict between the religious and the secular. Secularity affects not only the legal and political order but also the educational project proposed by the State, as education is regulated and implemented by the government through specific policies. Therefore, we understand that a declared secular and democratic State is the result of a civilizing process, from which a pedagogical project is expected to reflect the inherent assumptions of what is declared. Thus, according to the presented framework, the research aims to answer the following guiding question: how does the modern project of secularizing the world impact education? It should be noted that the dissertation falls within the field of discussion related to the history of pedagogical ideas. The overall objective, implied in the guiding question, is to analyze how the modern project of secularization affects education. As proposed by the general objective, the following specific objectives are highlighted: first, to conceptualize secularization and secularity; second, to develop the modern understanding of secularity and secularization; and third, to understand education and secularity according to the assumptions of Modernity. The research is theoretical in nature and will be conducted through the analytical reading of the collected bibliographic material. The work will proceed with the analysis of selected works and articles that will contribute to the construction of the research. In order to reconstruct a theme related to pedagogical theory, we analyze through the sociological theories of Modernity a reconstruction of the history of the central concepts of the research, as proposed by Koselleck (2020). The research presents a chapter division scheme, reflecting the specific objectives, in order to achieve the overall objective. The first chapter is titled "Secularization and Secularity: delimitation of concepts" and seeks to highlight that secularization is a broader process than secularity, as it is linked to society as a whole, while secularity is subordinate to the political-juridical sphere of the formation of Law and the State, presenting its derivations: secularization and secularism, with secularism being a combative secularity, characteristic of the French secularization process, directly related to education. The second chapter, "Modernity and Secularity," develops the historical and conceptual understanding of Modernity and its understanding of secularity and the process of secularization. Modernity incorporates secularity as a fundamental concept for the formation and organization of the State, governed autonomously and separated from all ecclesiastical or religious dogmatic authority. The third chapter, entitled "Modernity and Secular Education," seeks to identify, according to the described modern understanding, the relationship between education and secularity, in a way that the former cannot be understood without the latter, reflecting a modern pedagogical thought for which a secular education is indispensable. Finally, with the concluding remarks, we highlight modern assumptions that still persist in the ideal we have, as a society, of secular schools and education. We assert that secularity and education are inseparable pillars in Modernity, seeking to reconcile individual freedom with social responsibility by promoting an education based on universal, ethical, and civic values, regardless of individuals' religious beliefs, playing a fundamental role in the formation of autonomous, critical, and tolerant citizens, and contributing to the construction of democratic, pluralistic, and egalitarian societies.